Drought stress and soil management practices in grapevines in Cyprus under the threat of climate change - Chrysargyris, Antonios; Xylia, Panayiota; Litskas, Vassilis D.; Mandoulaki, Athanasia; Antoniou, Demetris; Boyias, Timos; Stavrinides, Menelaos; Tzortzakis, Nikos G. (My University, 2018)
The Middle East, the cradle of viticulture and wine production, is gradually but steadily becoming hotter and drier because of climate change (CC). In the current study, we evaluated the effect of tillage and irrigation on yield and quality characteristics of the heat-resistant, indigenous red-grape variety Maratheftiko for one year. Yield increased (two-fold) in vines with irrigation and tillage compared to tillage with no irrigation. The absence of tillage buffered the negative effect of the lack of irrigation on yield. At the veraison stage, leaf stomatal conductance decreased in non-irrigated vines, independently of the application of tillage or not. At veraison, tillage increased (up to 27.5%) phenolics when compared to no tillage in non-irrigated vines. Vines accumulated more N, P, and K and less Mg during the flowering stage compared to veraison. At veraison, irrigation decreased K content in vines subjected to tillage and decreased Mg content in vines subjected to no tillage. Total soluble solids and anthocyanins of berries increased with the absence of irrigation and tillage. Total phenolics increased with tillage in both irrigated and non-irrigated plants. Our results indicate that no tillage systems may be viable as an adaptation strategy in the context of CC.
Keywords: Cultivation practices; Grapes; Irrigation; Phenolics; Quality; Tillage